Evaluation in the Teaching Practicum of the English Program at the Universidad de la Amazonía - Claudia Rodríguez Ferreira (Universidad Nacional de Colombia, 2009)
The following article summarizes the research study which sought to examine the process of evaluation in the teaching practicum of the undergraduate program in English language teaching at Universidad de la Amazonía, in Florencia, Caquetá, Colombia. The purpose of this project was to establish which evaluation paradigm promotes the professional development of the student teacher whilst inside the actual conditions of her/his work. The research process was based on participant, non- participant observations and interviews with a group of 17 student teachers and their counsellor. The results showed some features of the critical paradigm of evaluation that contributed to the professional development of the subjects involved in the practicum (student teachers and counsellor). It was also found that it is very important to encourage the formation of critical and progressive professionals.